Repair of a Large Nasal Ala and Medial Cheek Defect: Case Report - Hannah E. Myers; Ashley A. Kessler; Michael Roberts; Christopher Buckley (Karger Publishers, 2024)
Introduction: Mohs micrographic surgery is a complex but essential aspect of functional and cosmetic skin cancer removal. It allows for skin cancers to be removed from cosmetically challenging areas in the most efficient and effective possible method; however, closure of these lesions can be difficult. Case: An 80-year-old male presented for Mohs surgery of a basal cell carcinoma on the right nasal sidewall that measured 3.4 cm. The patient underwent seven stages of Mohs surgery, and the final defect measured 6.5 cm × 5.5 cm, resulting in a large area for closure with multiple cosmetic and functional units affected. Discussion: This case discusses options for complex closure of large defects on the nose and the reasoning behind the final choice in closure.